Inter-Observer Variability in Target Volume Delineations of Benign and Metastatic Brain Tumours for Stereotactic Radiosurgery: Results of a National Quality Assurance Programme. Issue 1 (January 2020) - Growcott, S.; Dembrey, T.; Patel, R.; Eaton, D.; Cameron, A.
Abstract: Aims: To quantify inter-observer variation between all the intracranial stereotactic radiosurgery (SRS) providers in England in delineating the target volumes of four brain tumour cases. Materials and methods: Twenty-two, cross-platform SRS providers in England were instructed during a national commissioning assessment to contour the gross tumour volume (GTV) of six brain metastases, one cavernous sinus meningioma, one vestibular schwannoma and one pituitary adenoma. An expert reference group provided feedback if submitted contours were considered to be outliers and those centres were instructed to resubmit their contours. All contours were analysed in Python. The target volume contour (observed volume; VOBS ), encompassing volume, 50% agreement volume (AV50 ), 100% agreement volume (AV100 ), concordance index (CCI) and discordance index (DCI) were calculated. Results: Twenty-one centres participated using five different treatment platforms (CyberKnife, Gamma Knife, Varian Linac, Elekta Linac, Tomotherapy) and seven different treatment planning systems (GammaPlan, iPlan, Multiplan, Pinnacle, Eclipse, CMS Focal). The greatest variability was observed in the smallest brain metastases (GTV5 AV50 0.0 cm 3, CCI 0.28–0.84, DCI 0.00–0.70) and pituitary case (AV50 1.1 cm 3, CCI 0.42–0.82, DCI 0.01–0.40). The greatest agreement was observed with the vestibular schwannoma (AV50 2.8 cm 3, CCI 0.77–0.94, DCI 0.00–0.17). There were four resubmissions for the cavernous sinus meningioma and three resubmissions for the pituitary adenoma. Conclusions: Inter-observer variability was most evident with the smallest brain metastases and pituitary case. Several additional outliers and one acceptable contour were suggested using the metric-based analysis of AV50, CCI and DCI. Comparing contours using these metrics is an effective way to identify whether individual contours are similar to the 'true' target and to flag potentially significant deviations. Highlights: National, multicentre study of all stereotactic radiosurgery centres in England. Evidence of inter-observer variability across a national population. Variability most evident with the smallest volumes and geometrically complex targets. Peer review highlighted inconsistencies in identifying acceptable and outlying contours. AV50, CCI and DCI metrics can be used to identify outliers of benchmarking cases.